2008
DOI: 10.1534/genetics.107.086249
|View full text |Cite
|
Sign up to set email alerts
|

A SUMO-Like Domain Protein, Esc2, Is Required for Genome Integrity and Sister Chromatid Cohesion in Saccharomyces cerevisiae

Abstract: The ESC2 gene encodes a protein with two tandem C-terminal SUMO-like domains and is conserved from yeasts to humans. Previous studies have implicated Esc2 in gene silencing. Here, we explore the functional significance of SUMO-like domains and describe a novel role for Esc2 in promoting genome integrity during DNA replication. This study shows that esc2D cells are modestly sensitive to hydroxyurea (HU) and defective in sister chromatid cohesion and have a reduced life span, and these effects are enhanced by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…ESC2 encodes a protein containing two SUMO-like domains [6][8] and plays a role in sister chromatid cohesion in conjunction with Smc5-Smc6 in the repair of damage during DNA replication [39], [40]. Deletion of ESC2 also causes a strong defect in suppressing GCRs, particularly duplication-mediated GCRs, though less than that caused by the mms21-11 allele (Table 1) [5].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ESC2 encodes a protein containing two SUMO-like domains [6][8] and plays a role in sister chromatid cohesion in conjunction with Smc5-Smc6 in the repair of damage during DNA replication [39], [40]. Deletion of ESC2 also causes a strong defect in suppressing GCRs, particularly duplication-mediated GCRs, though less than that caused by the mms21-11 allele (Table 1) [5].…”
Section: Resultsmentioning
confidence: 99%
“…Both MMS21 and ESC2 suppress duplication-mediated GCRs (Table 1), are epistatic with each other (Table 1), and prevent the formation of X-shaped DNA replication intermediates [7], [39], [40]. Esc2 contains SUMO-like domains and no known enzymatic activity [6], but physically interacts with components of the SUMO pathway, including Ubc9 and Smt3 itself [7]. Previous studies of Rad60, an ortholog of Esc2 in fission yeast, identified an interaction between Rad60 and the Smc5-Smc6 complex and showed that Rad60 functions in the same pathway as Nse2, the fission ortholog of Mms21 [59], [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that Smc5/6 accumulates at the sites of DNA double-strand breaks or collapsed replication forks (Lindroos et al, 2006). S. cerevisiae ESC2 is a putative homolog of rad60, and has been shown to be involved in chromatin silencing and sister chromatid cohesion (Dhillon and Kamakaka, 2000;Ohya et al, 2008). However, there is no evidence that S. pombe Smc5/6 has similar activity, and a correlative interaction between ESC2p and Smc5/6 has not been reported.…”
Section: Stable Cds1mentioning
confidence: 99%
“…The hydroxyurea (HU) and methyl methanesulfonate (MMS) act as replication checkpoint inhibitor and DNA damaging agent respectively. The Rrm3 mutant reported to have slightly sensitive phenotype in the 200mM hydroxyurea (22). With regard to SAF1 mutant the data is not available.…”
Section: Resultsmentioning
confidence: 99%